Scaling-Up Climate Smart Agricultural Technologies and Approaches Using Travelling Seminar as a Method and Tool in Nepal - Local Initiatives for Biodiversity, Research and Development (2019)
This policy brief describes the Local Initiatives for Biodiversity Research and Development (LI-BIRD) /Climate Change Agriculture and Food Security (CCAFS) experience of travelling seminar. The scaling Up of Climate Smart Agriculture (CSA) technologies and practices beyond the pilot sites has been a major challenge for government and non-government organizations. The travelling seminar was conducted in the farmers field with the participation of elected leaders especially women leaders with the objective of scaling up the CSA technologies beyond the pilot sites. The travelling seminar appears to be an appropriate tool to facilitate the adoption of CSA technologies and providing awareness and knowledge to government representatives on these technologies and practices and enabling them to use the seminar learning for influencing government decisions for climate and gender sensitive agriculture plans and programmes.